197k views
5 votes
If f(x)=6x^2-4 and g(x) =2x+2,find (f-g) (x).

User Jason FB
by
5.2k points

2 Answers

6 votes

Answer:

6x^2-2x-6 don't listen to these words it has to be 20 characters long

User Murki
by
5.2k points
4 votes

Answer:


\large\boxed{(f-g)(x)=6x^2-2x-6}

Explanation:


(f-g)(x)=f(x)-g(x)\\\\f(x)=6x^2-4,\ g(x)=2x+2\\\\\text{substitute:}\\\\(f-g)(x)=(6x^2-4)-(2x+2)\\\\=6x^2-4-2x-2\qquad\text{combine like terms}\\\\=6x^2-2x+(-4-2)\\\\=6x^2-2x-6

User Evgenii Zhuravlev
by
5.1k points